Manajemen Kurikulum dalam Meningkatkan Kualitas Pembelajaran di SMK Dwija Bakti 2 Jombang - Wafa, M. Aliyul; Sari, Nilla Bunga (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The background to this research is a lack of focus on the learning process that encourages students' thinking abilities at MA PK Sunan Ampel Nganjuk. In this research, the researcher aims to apply learning using the Problem Based Learning method. Problem Based Learning, called PBL, is a learning model that is student-centered by confronting students with various problems they face in their lives. learning that begins with a problem, where learning is essentially a process, namely a process that regulates and organizes the environment around students so that it can grow and encourage students to carry out the learning process. The learning process occurs because there is a goal to be achieved. The objectives in question are in the form of learning outcomes. This illustrates that what is the focus for educators is how to manage learning so that it can achieve the desired level of learning outcomes. Researchers use qualitative classroom action methods, with data collected through observation, tests and documentation. The observation process was carried out during the implementation of the action as an effort to find out the progress of the learning implementation at MA PK Sunan Ampel Nganjuk. Collecting data using tests by providing an essay worksheet with a total of 5 questions is given at each meeting to improve student learning outcomes. The research results show that the application of the Problem Based Learning model can improve student learning outcomes in class XI Madrasah Aliyah Plus Skills Sunan Ampel Nganjuk.